Challenges faced in the peer review system in open access journals - Kumar, Arun; Shah Newaz Ahmed (Asian Journal of Medical Sciences, 2022)
The whole mechanism of academic journal’s peer review system process effectively depends on how editors manage the journal work. The handling of the peer review system will determine how stupendously the reviewers are dedicated to the peer review system and it impacts the reputation of the journal’s timely publication. Ideally there should be a centralized system and have a clear stages of peer review, but often journals make the system harder than it is needed, either due to overly complex process or lack of coordination among the editor and the reviewers. On one hand the researchers spend a lot many years in studying a hypothesis or a novel concept, preparing themselves for some ground breaking findings assuming to make an impact in their field of study, but when it comes for publication, it is one of the biggest hurdle they need to overcome. Only after a trustworthy peer review process, the research article would find a space in a journal for publication. Struggle to find Qualified Reviewers It is a major struggle for an editor to find reviewers who are willing to perform peer reviews, but it is also difficult to find qualified reviewers who are competent enough to make criticisms in the manuscripts. There will always be a pool of academicians who are willing to be in the editorial board and to be a part of peer review, but finding and selecting qualified professionals with specific knowledge in the scope of publication is the real challenge for an editor. Sometimes there is a pressure to publish issue quickly within the time schedule, and then there are no excuses for lagging editorial development. So there is a need of timely review within the allocated time. When it comes to double blind peer review, the editor must be careful because sometimes the authors make recommendation for suggested reviewers who could be known to them with intent to overcome the review system. The Waiting begins The editor’s frustrations with the peer review systems begin when the deadlines are given to the reviewers to complete the manuscript evaluations, but it is not met with the timely response by the reviewers. Sometimes, the reviewer’s seldom responds to review requests. This is eventually noticed by the editors when the deadlines are completed and pop-up message comes to the editors. Unfortunately, the editors have to prepare themselves and re-assign to external reviewers and reset the deadlines to the authors for completion of review. This is the major reason, why the loyal and punctual reviewers are so highly valued for academic publications. Many a times, it might so happen that the selected reviewers are simply too busy in their academic commitments, so the request to review is denied by them. This denial is better as it saves times for the peer review process as the editor assigns to another potential reviewer. The things become worst for the editor, when the reviewers agree to complete the assigned task of reviewing but they do not respond even when the deadline is completed. On the other hand, the authors are eagerly waiting for the decision of their submitted manuscripts. The peer review matter is more problematic as most of the publications require minimum of two peer reviews before an editorial decision can be made. Therefore, the peer reviewed journals usually take more time for proper peer review process to get fulfilled. Retainment and Reformation of Editorial board Yet another obstacle for editors is urging the reviewers to remain in the editorial board. Those reviewers, who are really busy, put the peer review duties to the bottom of their priorities they pass the manuscript to their junior colleagues or subordinates, which effects the quality of review. The editors continually search for qualified reviewers, while at the same time they have to keep motivated the existing reviewers and board members for future evaluations. Those reviewers, who are honest and dedicated, are loaded with more articles for review which further deteriorates the quality of review. On the other side, the editors have to reform the entire editorial board time to time, in order to fill up with qualified and dedicated reviewers and remove those who have not performed any reviews. Initially the reviewers are enthusiastic but with time, they become sluggish and get demotivated. Frustration of Authors When the authors submits their articles with the journal, they are usually told about the turnaround time from submission to publication, or approximately how long will the peer review process take. Eventually, if the review reports are not generated within the deadline, they have to wait until the review is completed. Some of the authors who need publication for promotions become restless and this delay can seriously burden young scholars and academicians for their career growth and academic advancements. Allocating External Reviewers Sometimes peer reviewers fail to understand the article is a comprehensive manner and inserts lots of criticism in the article with multiple flaws for which the editor are criticised and they have to apologize to authors for ineffective review. In such cases, the editor has to re-assign the article to the external reviewers for unbiased reviews How to overcome these obstacles and challenges The editors can establish some means for proper recognition of the reviewers who have contributed enormously in the peer review, by issuing the certificate of Peer Reviewer or enlisting their names on the website. It is often practiced to include the name of the peer reviewer in the published manuscript which can encourage more reviewer’s participation. The editors can decrease the turnaround time for manuscript evaluations and this can be eventually met by adopting a fast track review system. In this the assigned reviewers gets paid and the review time is shortened. This is usually practised to meet the demand and expectations of the authors. Alternatively, a novel publication system based on remuneration as well as recognition for qualified reviewers may help in development of a sustainable model for growth in academic research. Being a radical shift in publication ethics, such changes need wide consensus in academic circle before adoption. However, such reward driven system (both monetary and intellectual) can go a long way in redeeming the lacunae plaguing the current publication system. Despite of all the obstacles faced in the peer review, those journals which have such system are always given importance. If the peer review is not adopted, there would be a constant degradation of quality of articles published. It is important for authors to learn the value of the peer review system and respect the recommendation of reviewer and the decision made by the editors, even though if it may take a longer time.